2021
DOI: 10.1002/smtd.202101296
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐Drying and Atomic Layer Deposition: Complementary Tools toward Fully Orthogonal Control of Bulk Composition and Surface Identity of Multifunctional Supraparticles

Abstract: Spray‐drying is a scalable process enabling one to assemble freely chosen nanoparticles into supraparticles. Atomic layer deposition (ALD) allows for controlled thin film deposition of a vast variety of materials including exotic ones that can hardly be synthesized by wet chemical methods. The properties of coated supraparticles are defined not only by the nanoparticle material chosen and the nanostructure adjusted during spray‐drying but also by surface functionalities modified by ALD, if ALD is capable of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Spray drying being a cost‐effective and ton‐level strategy, has been widely reported effective in the construction of composites secondary particles. [ 18 ] After matching SiO x with HC, SC, and Gr, the secondary particles were constructed under the binding of sucrose ( Figure a). The final products after carbonization were labeled as HCSP, SCSP, and GrSP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Spray drying being a cost‐effective and ton‐level strategy, has been widely reported effective in the construction of composites secondary particles. [ 18 ] After matching SiO x with HC, SC, and Gr, the secondary particles were constructed under the binding of sucrose ( Figure a). The final products after carbonization were labeled as HCSP, SCSP, and GrSP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that this reduction results from vanishing of the interstitial pores between the assembled NCPs within the SP, as similarly observed in a previous study. [ 54 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that this reduction results from vanishing of the interstitial pores between the assembled NCPs within the SP, as similarly observed in a previous study. [54] Finally, a proof of concept for the temperature indicator functionality of the presented SPs is provided by comparing their spectral magnetic signature via MPS before and after the temperature event (Figure 2b5). On the logarithmically scaled y-axis, it is observed that the harmonic amplitude as a function of higher harmonics decays faster after temperature exposure (red circles) compared to the reference state (as prepared, blue squares).…”
Section: Proof Of Concept: Recording Temperature With Magnetic Suprap...mentioning
confidence: 99%
“…[ 82,83 ] Furthermore, advanced physical and chemical surface layer deposition methods could also be exploited for post‐synthetic surface modifications. Using atomic layer deposition, porous spray‐dried iron oxide particles, [ 84 ] as well as amorphous drug‐loaded particles, [ 85 ] have recently been successfully surface‐modified with various metal oxide (Al 2 O 3 , ZnO, and TiO 2 ) coatings. In general, post‐synthetic surface functionalization may circumvent spray‐drying‐inherent material limitations (see 2.2.)…”
Section: Spray‐drying As a Highly Versatile Tool For Materials Chemistsmentioning
confidence: 99%